Examples of Concepts of the Perfect Personality in the Art of Karakalpak Folklore - Aytmuratova Ziba Jalgasovna (Genius Publishing Group, 2023)
This article reflects the role and significance of Karakalpak folklore in the upbringing of the future generation as a perfect person. Folklore works that artistically interpret the worldview, socio-political, spiritual and philosophical views of our people in their own way are considered an extremely rare source, including many genres. Karakalpak folklore has its own long history, and in each of its lines we write meaningful words of encouragement in the question of the perfect man. In addition, the importance of Karakalpak proverbs in the development of spiritual knowledge in the minds of the mature generation, in the education of a perfect person, in the formation of national abilities is investigated
Keywords: proverbs; upbringing; harmonious development; moral perfection